2017
DOI: 10.1002/hbm.23565
|View full text |Cite
|
Sign up to set email alerts
|

Connectivity patterns during music listening: Evidence for action‐based processing in musicians

Abstract: Musical expertise is visible both in the morphology and functionality of the brain. Recent research indicates that functional integration between multi-sensory, somato-motor, default-mode (DMN), and salience (SN) networks of the brain differentiates musicians from non-musicians during resting state. Here, we aimed at determining whether brain networks differentially exchange information in musicians as opposed to non-musicians during naturalistic music listening. Whole-brain graph-theory analyses were performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
2

Relationship

5
4

Authors

Journals

citations
Cited by 86 publications
(75 citation statements)
references
References 118 publications
(127 reference statements)
4
62
0
4
Order By: Relevance
“…Listening to music also showed significant changes in rs-FC of the e-PNN in healthy controls (Karmonik et al, 2016; Brodal et al, 2017; Alluri et al, 2017). However, the connectivity patterns show solely the after effects of listening to music and differ from those identified in the FM patients, starting with a right lateralization of the significant changes, compared to the left lateralization in FM.…”
Section: Discussionmentioning
confidence: 94%
“…Listening to music also showed significant changes in rs-FC of the e-PNN in healthy controls (Karmonik et al, 2016; Brodal et al, 2017; Alluri et al, 2017). However, the connectivity patterns show solely the after effects of listening to music and differ from those identified in the FM patients, starting with a right lateralization of the significant changes, compared to the left lateralization in FM.…”
Section: Discussionmentioning
confidence: 94%
“…It has been shown that some short-term plastic changes can even occur in the case of merely listening to music-without actually performing-(e.g., [95]) and in the short-time perspective of both listening and performing (e.g., [96]). Attentive listening to music in a real-time situation, in fact, is very demanding: it recruits multiple forms of memory, attention, semantic processing, target detection and motor function [18,97]. As such, we propose here that music represents a sort of enriched environment that invites the brain to raise its general level of conscious functioning.…”
Section: Discussionmentioning
confidence: 98%
“…Besides auditory cortices, also motor regions, such as the supplementary motor area and the cerebellum, are involved during musical activities, including both playing and listening. Due to audio-motor coupling that is necessary for playing an instrument, listening is influenced by the motor demands intrinsic to musical practice, even to the extent that this would become manifest also in the brain responses to music listening alone [18,19]. Moreover, practising and performing music is a complex, multimodal behaviour that requires extensive motor and cognitive abilities.…”
Section: Introductionmentioning
confidence: 99%
“…For example, PreCG and PostCG are linked to experiencing tension, expectancy, and anticipation (Bjork & Hommer, 2007;James, Michel, Britz, Vuilleumier, & Hauert, 2012;Lehne et al, 2014;Thaut et al, 2014;Vuilleumier & Trost, 2015). Also, the PCUN is used in evaluating music's continuous structure, making perception-based predictions, and entrainment (Alluri et al, 2017;Trost et al, 2014). Thus, activity in the PreCG, PostCG and PCUN could be involved in processing musical structure and predicting future music events, alongside emotions such as tension, anticipation and expectancy.…”
Section: Brain and Emotional Responses To Pre-dropmentioning
confidence: 99%